An insight into the sialome of Glossina morsitans morsitans - Alves-Silva, Juliana (BioMed Central, 2010)
BACKGROUND: Blood feeding evolved independently in worms, arthropods and mammals. Among the adaptations to this peculiar diet, these animals developed an armament of salivary molecules that disarm their host's anti-bleeding defenses (hemostasis), inflammatory and immune reactions. Recent sialotranscriptome analyses (from the Greek sialo = saliva) of blood feeding insects and ticks have revealed that the saliva contains hundreds of polypeptides, many unique to their genus or family. Adult tsetse flies feed exclusively on vertebrate blood and are important vectors of human and animal diseases. Thus far, only limited information exists regarding the Glossina sialome, or any other fly belonging to the Hippoboscidae. RESULTS: As part of the effort to sequence the genome of Glossina morsitans morsitans, several organ specific, high quality normalized cDNA libraries have been constructed, from which over 20,000 ESTs from an adult salivary gland library were sequenced. These ESTs have been assembled using previously described ESTs from the fat body and midgut libraries of the same fly, thus totaling 62,251 ESTs, which have been assembled into 16,743 clusters (8,506 of which had one or more EST from the salivary gland library). Coding sequences were obtained for 2,509 novel proteins, 1,792 of which had at least one EST expressed in the salivary glands. Despite library normalization, 59 transcripts were overrepresented in the salivary library indicating high levels of expression. This work presents a detailed analysis of the salivary protein families identified. Protein expression was confirmed by 2D gel electrophoresis, enzymatic digestion and mass spectrometry. Concurrently, an initial attempt to determine the immunogenic properties of selected salivary proteins was undertaken. CONCLUSIONS: The sialome of G. m. morsitans contains over 250 proteins that are possibly associated with blood feeding. This set includes alleles of previously described gene products, reveals new evidence that several salivary proteins are multigenic and identifies at least seven new polypeptide families unique to Glossina. Most of these proteins have no known function and thus, provide a discovery platform for the identification of novel pharmacologically active compounds, innovative vector-based vaccine targets, and immunological markers of vector exposure.